Residential location and mobility of registered sex offenders - Mustaine, Elizabeth E. (American journal of criminal justice, 2006)
Identifying the residential locations of registered sex offenders is a major concern for contemporary policy makers and communities. The present study seeks to identify whether registered sex offenders’ residential locations at time of arrest differ from their current addresses, if registrants move whether they tend to move to more or less socially disorganized neighborhoods, as well as what factors are associated with moving to more or less socially disorganized areas. Data are analyzed for 271 registrants on 11 measures of community social disorganization variables. Findings indicate that registrants already residing in socially disorganized areas were less likely to have a downward movement to more socially disorganized areas. Also, those who resided in less socially disorganized areas initially were more likely to have downward movement to socially disorganized areas.